A single-cell atlas reveals the heterogeneity of meningeal immunity in a mouse model of Methyl CpG binding protein 2 deficiency - Li, Huiping; Hu, Meixin; Huang, Zhuxi; Wang, Yi; Xu, Ying; Deng, Jingxin; Zhu, Ming; Feng, Weijun; Xu, Xiu (Frontiers in Immunology, 2023)
Methyl CpG binding protein 2 (MeCP2) is a DNA methylation reader protein. Mutations in MeCP2 are the major cause of Rett syndrome (RTT). Increasing evidence has shown that dysregulated immunity and chronic subclinical inflammation are linked to MeCP2 deficiency and contribute to RTT development and deterioration. The meninges surrounding the central nervous system (CNS) contain a wide repertoire of immune cells that participate in immune surveillance within the CNS and influence various brain functions; however, the characterization and role of meningeal immunity in CNS with MeCP2 deficiency remain poorly addressed. Here, we used single-cell sequencing to profile Mecp2 deficient meningeal immune cells from the dura mater, which has been reported to contain the most meningeal immune cells during homeostasis. Data showed that the meninges of Mecp2-null mice contained the same diverse immune cell populations as control mice and showed an up-regulation of immune-related processes. B cell populations were greater in Mecp2-null mice than in control mice, and the expression of genes encoding for immunoglobulins was remarkably higher. Mecp2 deficient meninges also contained more cytotoxic CD8+ T cells than control meninges. With increased interferon-γ transcription in T and natural killer cells, meningeal macrophages showed decreased suppression and increased activity in Mecp2-deficienct mice. Together, these findings provide novel insights into meningeal immunity, which is a less studied aspect of neuroimmune interactions in Mecp2-mutated diseases, and offer an essential resource for comparative analyses and data exploration to better understand the functional role of meningeal immunity in RTT.